SOEKARNO DAN PEMIKIRANNYA TENTANG AGAMA, POLITIK, DAN PENDIDIKAN ISLAM - Muhamad Mawangir (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2016)
Soekarno is better known not as an expert on religion and education, but as a political figure and leaders of this nation. However, that does not mean Soekarno did not have the concept of religion and education. Based on literature data searches by the author, the author encountered a number of ideas or thoughts Soekarno who come into contact with the area of religion and education are sourced from Soekarno views about Islam. In some writings, Sukarno many calls and identify the various problems faced by the Islamic world, especially with regard to cultural issues, low intellect and political phenomenon in various parts of the Islamic world. But Sukarno always believed, that if Muslims would be modern and upgraded, then Islam is no longer a religion in the sense of mere ritual, but Islam will be transformed into the power of transformation and change. Religion, politics and education according to Sukarno became the top priority to be implemented because it is in fact a decisive factor for the development of Muslims in Indonesia. Islam, which is believed to be the most perfect religion, place education as a very important aspect which requires his people. There is no other way to fix the slump Muslims besides preparing an education system which is rooted in the values, principles, objectives and political religion of Islam. The Soekarno thinking about religion that he conducted a series of efforts to release Muslims from its association to the interpretation or opinion among the scholars past and awaken Muslims to freedom to deal directly with the Qur'an and hadith through intellectual work. As well as provide space for the people to give rights to all of them to govern and regulate the way in solving the problems of Islamic education in Indonesia through The politically. Soekarno thought of religion, politics and Islamic education is always oriented towards the progress.